Antibacterial coaxial hydro-membranes accelerate diabetic wound healing by tuning surface immunomodulatory functions. (December 2022) - Zhang, Wei; Xia, Sizhan; Weng, Tingting; Yang, Min; Shao, Jiaming; Zhang, Manjia; Wang, Jialiang; Xu, Pengqing; Wei, Jintao; Jin, Ronghua; Yu, Meirong; Zhang, Zhongtao; et al.
Abstract: Diabetic foot ulcers, typical non-healing wounds, represent a severe clinical problem. Advanced glycation end-products (AGEs), which create a prolonged pro-inflammatory micro-environment in defective sites, can be responsible for refractoriness of these ulcers. Macrophages are polarized to the M2 phenotype to facilitate the transition from a pro-inflammatory microenvironment to an anti-inflammatory microenvironment, which has been demonstrated to be an effective way to accelerate diabetic wound closure. Herein, we developed coaxial hydro-membranes mimicking the extracellular matrix structure that are capable of anti-inflammatory and antibacterial functions for diabetic wound repair. These fibrous membranes maintain a moist microenvironment to support cell proliferation. Macrophages grow in an elongated shape on the surface of the fibrous membranes. The fibrous membranes effectively impaired macrophage AGE-induced M1 polarization and induced macrophage polarization towards the M2 phenotype. The effects of the fibrous membranes on the interactions between macrophages and repair cells under a diabetic condition were also investigated. Furthermore, in vivo results from a full-thickness diabetic wound model confirmed the potential of the coaxial hydro-membranes to accelerate wound healing. This study's results indicate that the developed bioactive anti-inflammatory and antibacterial wound dressing can affect AGE-induced macrophage activation and crosstalk between macrophages and fibroblasts for treating diabetic wounds. Graphical abstract: Image 1